Business cycles, unemployment and entrepreneurial entry: First evidence from Germany - Michael Fritsch; Alexander Kritikos; Katharina Pijnenburg (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
We investigate whether people become more willingly self-employed during boom periods or in recessions and to what extent it is the business cycle or the employment status influencing entry rates into entrepreneurship. Our analysis for Germany reveals that start-up activities are positively influenced by unemployment rates and that the cyclical component of real GDP has a negative effect. This implies that new business formation is counter-cyclical. Further disentangling periods of low and high unemployment periods reveals a low unemployment retard effect.
Keywords: L26; E32; 330; business cycle; self-employment; start-up; unemployment